Definition of the Response to Initial Therapy with Radioiodine in Patients with Differentiated Thyroid Carcinoma: Basal or Stimulated Thyroglobulin? - Rosario, Pedro Weslley; Mourão, Gabriela Franco; Calsolari, Maria Regina (Hormone and Metabolic Research, 2019)
Basal thyroglobulin (b-Tg) measured with second-generation assay or stimulated Tg (s-Tg) can be used to define the response to therapy of differentiated thyroid carcinoma. However, they do not always define the same category and guidelines do not establish “if” or “when” s-Tg needs to be obtained. We studied 304 patients without clinically apparent disease or disease detected by neck ultrasonography and without anti-Tg antibodies 9–12 months after therapy. Based on b-Tg, 196 patients had an excellent response and 108 had an indeterminate response. Based on s-Tg, a change in category occurred in 10.2% of the patients with an initial excellent response (all to indeterminate response) and in half the patients with an initial indeterminate response (44.4% to excellent response and 5.5% to biochemical incomplete response). One case of recurrence was observed among patients with an initial excellent response but whose response changed to indeterminate after s-Tg, while no disease was detected among those who remained in the initial category; however, this difference was not significant. In patients with an initial indeterminate response, no recurrence was detected among those whose response changed to excellent after s-Tg, while 11.1 and 33.3% of those who remained in the initial category or whose response changed to biochemical incomplete, respectively, had structural disease. This study suggest that, in low- or intermediate-risk patients, s-Tg better defines the response to therapy with 131I when it is classified as indeterminate based on b-Tg using second-generation assay. However, s-Tg is not necessary when b-Tg defines the response as excellent.
Keywords: differentiated thyroid carcinoma; response to therapy; thyroglobulin; stimulation; recurrence